Pixação e as linguagens visuais no bairro Benfica: uma análise dos modos de ocupação de pixos e graffiti e de suas relações entre si - Chagas, Juliana Almeida (2015)
This research focuses on the analysis of the practices of pixação and graffiti and their relations in the city of Fortaleza-CE. This study was field delimitation Benfica neighborhood and through an ethnographic methodology the streets and avenues of this neighborhood were covered by hikes that have focused on the observation and recording, through photographs, pixos signs, graffiti and advertising. We question how these interventions occupy the city and how they relate to each other. The walls had relations, mostly conflicting from a competition for visibility. From the field and speaks of the interlocutors was made discussions about the following relationships: sewing, trampling, erasure, suffocation and coverage. The narratives also triggered differentiation in the boundaries between pixação, graffiti and urban art. In addition to the agonistic that permeate these fields, the action of reframe the city by these languages was seen from the contributions of Rancière and other authors as Foucault and Agamben as dissent scenes or resistance of micro enabling power rearrangements, challenging the forces of discipline and standardization.